Restaging Hysteria: Mary Wigman as Writer and Dancer - Laura A. McLary (Studies in 20th & 21st Century Literature, 2003)
Mary Wigman was not only a leading proponent of the early twentieth-century Expressionist dance movement, but also a writer of poetry and short poetic prose. Despite her assertion that dance was beyond language, she wrote often about dance in an attempt to articulate the kinesthetic experience of dance through languages. This interdisciplinary study explores the intersection of dance and writing for Wigman, focusing on gender coding in writing and dance within the context of early twentieth-century dialogues. Despite the pervasive equation of (feminine) hysteria with dance and (masculine) subjectivity with authorship, Wigman engaged in both activities. I argue that Wigman is able to reclaim and redefine the "hysteria" of the dance experience through writing about dance. In her dance poetry, the act of looking at herself in a mirror as she dances allows Wigman to circumvent the traditional objectification through the male gaze experienced by the female dancer. Through the act of writing, Wigman asserts her subjectivity, taking control of the out-of-body experience of dance creation.
Keywords: Mary Wigman; twentieth-century; dance; expressionist dance; poetry; prose; short poetic prose; hysteria; kinesthetic experience; language; expression; intersection; gender coding; writing; feminine hysteria; masculine subjectivity; subjectivity; mirror; objectification; male gaze; female dancer; gender